Captive Equus Burchelli : female dominance and female aggression - Azrina Husain (2009)
This study examined whether female dominance is correlated to aggressive behaviors in female captive Equus burchelli zebras (N=5) in the Singapore Zoo. In particular, the relationship between dominance rank and rank distance with aggressive behaviors, which would be further, elaborated upon in the paper. Results were measured using sociomatrices software MatMan (De Vries, Netto & Hanegraaf, 1993) designed to test for matrix correlations. The results supported the hypothesis that dominant females displayed more aggression than female subordinates. In addition to that, female subordinates in the hierarchy received more aggression than dominant females within the group. Supporting these hypotheses is the findings that aggressive behaviors are also associated with rank distance.